Fabrication, structural, optical and magnetic characterizations of BiFeO3/GdFeO3 bilayer films - Baqiah, Hussein; Zhang, Na; Awang Kechik, Mohd Mustafa; Al-Asbahi, Bandar Ali; Yang, Jianlei; Li, Qiang; Xu, Shicai (Springer Science and Business Media Deutschland GmbH, 2026)
BiFeO3 (BFO) and GdFeO3 (GFO) are perovskite structured materials with rich physical properties. This work investigates the influence of annealing temperature (450, 550 and 600 °C) and the use of GFO buffer layer on the microstructural, optical and magnetic properties of BFO/GFO films synthesized by sol-gel spin-coating technique. The films were compared with that of BFO film annealed at 550 °C. From X-ray diffraction analysis, the introduction of GFO layer reduced the lattice parameters and enhanced the crystallinity, purity and particle growth of BFO layer. From atomic force microscopy analysis, the surface of BFO/GFO film annealed at 550 °C showed better particle shape uniformity and less porosity in comparing with BFO film. As the annealing temperature increased from 450 to 600 °C, the energy band gap (Eg) reduced from 2.73 to 2.64 eV. The Eg reduced from 2.71 eV for BFO film to 2.68 eV for BFO/GFO film. Intensity of photoluminescence peaks of the BFO/GFO film increased with the increasing of annealing temperature and with the introduction of GFO layer. The annealing temperature increasing led to enhance the BFO/GFO film magnetization (Ms). However, the BFO/GFO film exhibited a lower Ms 28.2 emu/cm3 compared to BFO film with Ms 29.6 emu/cm3.